Camallanus cotti (Nematoda: Camallanidae), an introduced parasite of fishes in New Caledonia - Moravec, Frantisek; Justine, Jean-Lou (Folia parasitologica, 2006)
A pathogenic Asian nematode species of Camallanus, C. cotti Fujita, 1927, was found in New Caledonia, South Pacific, for the first time; it was recorded from two native fishes, Awaous guamensis (Valenciennes) (Gobiidae) (prevalence 51%, intensity 1-25) and Kuhlia marginata (Cuvier) (Kuhliidae) (a single specimen found), of the La Foa River, about 100 km north of Nouméa; the latter represents a new host record. Morphological data on C. cotti based on New Caledonian specimens and those previously collected from aquarium-kept Misgurnus anguillicaudatus (Cantor) in Canada have been provided. The SEM examination of C. cotti, applied for the first time in this species, made it possible to study some of its morphological details; first-stage larvae from the female's uterus were found to possess several digit-like processes on the tail tip, not previously reported for any species of the Camallanidae. Camallanus moraveci Petter, Cassone et France, 1974 is considered a junior synonym of C. cotti. A list of hitherto recorded hosts of C. cotti is provided. Camallanus cotti is assumed to be introduced into New Caledonia along with the introduction of the exotic poeciliid fishes, which are known to be among the most common hosts of C. cotti in aquarium cultures worldwide.
Keywords: Rivers; Nová Kaledonie; Perciformes; Female; Nematoda; New Caledonia; hlístice; řeky; Animals; Microscopy, Electron, Scanning; ženské pohlaví; mužské pohlaví; Male; zvířata; mikroskopie elektronová rastrovací